Identification of signaling networks associated with lactate modulation of macrophages and dendritic cells - Rapeepat Sangsuwan; Bhasirie Thuamsang; Noah Pacifici; Phum Tachachartvanich; Devan Murphy; Abhineet Ram; John Albeck; Jamal S. Lewis (Heliyon)
The advancement in the understanding of cancer immune evasion has manifested the development of cancer immunotherapeutic approaches such as checkpoint inhibitors and interleukin agonists. Although cancer immunotherapy breakthroughs have demonstrated improved potency for cancer treatment, only a fraction of patients effectively respond to these treatments. Moreover, there is compelling evidence indicating that cancer cells develop a unique microenvironment through adaptive metabolic reprogramming, which aberrantly modulates host immunity to evade immunosurveillance. As part of the tumor cell adaptive metabolic switch, lactate is produced and released into the tumor environment. Recent studies have shown that lactate significantly modulates immune functions, especially in innate immune cells. Dendritic cells (DCs) and macrophages (MΦs) are specialized antigen-presenting cells serving as key players in innate immunity and anticancer-associated immune responses. Although most studies have shown that lactate affects immune phenotypes (e.g., surface protein expression and cytokine production), the cell signaling network mediated by lactate is not fully understood. In the present study, we identified the key signaling pathways in bone marrow-derived DCs and MΦs that were changed by cancer-relevant concentrations of lactate. First, transcriptome analysis was used to guide notable signaling pathways mediated by lactate. Subsequently, biomolecular techniques, including immunoblotting, flow cytometry, and immunofluorescence imaging were performed to corroborate the changes in these key signaling pathways at the protein level. The results indicated that lactate differentially impacted the biochemical networks of DCs and MΦs. While lactate mainly altered STAT3, ERK, and p38 MAPK signaling cascades in DCs, the STAT1 and GSK-3β signaling in MΦs were the major pathways significantly impacted by lactate. This study identifies key biochemical pathways in innate immune cells that are impacted by lactate, which advances our understanding of the interplay between the tumor microenvironment and innate immunity.